Panegyric Emblem Books, Jesuits and the Habsburg Emperors: Some Examples Related to 17th-Century Croatia - Milan Pelc (Radovi Instituta za Povijest Umjetnosti, 2019)
This article presents several printed collections of panegyric emblems related to the Croatian cultural milieu as specific media intended to promote the Habsburg imperial house in the 17th century. Emblem books were not printed in Croatia, but many of them were used, especially by Jesuits, as is documented in an 18th-century book inventory of the Zagreb Jesuit College’s library (preserved in Budapest). Some of these emblem books are dedicated to the Habsburg emperors Ferdinand III and Leopold I. The only author of an emblem book from Croatia in the 17th century was Sebastian Glavinić (1632–1697), Bishop of Senj, who was educated at the Jesuit academies in Graz, Vienna, and Trnava. In Vienna, he published an epithalamic panegyric emblem book in honour of the wedding of Leopold I and Margaret of Spain in 1666, under the title Deplua charitum aurora augustissimi Phoebi Leopoldi augusto rore in Margaritam resoluta. By glorifying the imperial wedding in a medium that was accessible to the wider public, Glavinić could himself partake in the imperial glory, which also brought him certain benefits.